A Cluster of Surprise Egg Toys as Designed Objects at the Intersection of Design and Culture [2] - Talu, N.; Talu, Nilüfer (Common Ground Research Networks, 2022)
This study examines the cultural context of a cluster of surprise egg toys. The cluster contains 167 toys, collected between the years 1993 and 2015. The study methodology consisted of content analysis involving both qualitative interpretation and quantitative techniques. The interpretation is initiated with the toys’ physical materiality. Analysis is then developed on the compositional modalities of each toy, the place of each in the cluster, and the cluster as a whole. Qualitative interpretation and theoretical analysis of detailed descriptions and groupings of the cluster highlight the central themes found at the intersection of design and culture. Analysis of the cluster reveals that it carries the duality, or the tension, between modern and postmodern cultures with one elevating functionality and the other using storytelling as a means of creativity. They are designed objects and design things blending the two cultures in their physical content, and can be seen as artifacts that contribute to the value of design in everyday life within the context of mass culture. © Common Ground Research Networks, Nilüfer Talu, All Rights Reserved.
Keywords: Culture; Design; Modern Culture; Postmodern Culture; Surprise Egg Toys; Toys